Catalytic synthesis of amides via aldoximes rearrangement. Issue 13 (11th December 2014) - Crochet, Pascale; Cadierno, Victorio
Abstract : This Feature article provides a comprehensive overview of the developments achieved in the catalytic synthesis of amides via rearrangement of aldoximes. Abstract : Amide bond formation reactions are among the most important transformations in organic chemistry because of the widespread occurrence of amides in pharmaceuticals, natural products and biologically active compounds. The Beckmann rearrangement is a well-known method to generate secondary amides from ketoximes. However, under the acidic conditions commonly employed, aldoximes RHCNOH rarely rearrange into the corresponding primary amides RC(O)NH2 . In recent years, it was demonstrated that this atom-economical transformation can be carried out efficiently and selectively with the help of metal catalysts. Several homogeneous and heterogenous systems have been described. In addition, protocols offering the option to generate the aldoximes in situ from the corresponding aldehydes and hydroxylamine, or even from alcohols, have also been developed, as well as a series of tandem processes allowing the access to N -substituted amide products. In this Feature article a comprehensive overview of the advances achieved in this particular research area is presented.